A Comparative Study Of Psychiatric Morbidity In Dermatological Patients - Sharma Neelu; Koranne Raviender V; Singh R K (Wolters Kluwer Medknow Publications, 2003)
The psychiatric morbidity in five chronic and disfiguring diseases, namely psoriasis, chronic urticaria, leprosy, vitiligo and lichen simplex chronicus (LSC) was assessed and compared using the standardized Hindi (Vernacular languages) version of General Health Questionnaire (GHQ-H). Thirty new untreated patients of each of the above skin diseases between the age group of 18-60 years were included in the study. The overall prevalence of the psychiatric morbidity was found to be 39%, depression and anxiety were present in 13% and 10.66% of the patients and suicidal ideations and somatisation in 16% and 13% of the patients respectively. Prevalence of interpersonal conflict and suicidal attempt were 10% and 2.6% respectively. On comparative analysis of psychiatric morbidity, significant difference was observed between vitiligo and other disorders (p=0.0028), i.e., chronic urticaria (p=0.0242) and psoriasis and other disorders (p=0.0028), however no significant difference could be elicited between psoriasis and leprosy or leprosy and vitiligo. Comparative analysis of anxiety revealed statistically significant difference between the patients of LSC and vitiligo (p=0.02) or vitiligo and chronic urticaria (p=0.04) but no significant difference was observed for vitiligo and leprosy of psoriasis and leprosy. The prevalence of somatic complaints showed significant difference between the patients of LSC and Leprosy.